Skill standards for biotechnology graduates in Malaysia: an industrial perspective - Loke, Choy Yean (2008)
21st century is seen as a biotechnology era and Malaysia aspires to be a biotechnology hub which is clearly spelled out in the National Biotechnology Policy (NBP). In order to rationalise this ambitious plan, the quality of human resources is identified as vital in order to succeed its growth and development. Since there are worries about how well biotechnology graduates get prepared in the real working environment, the purpose of this study was to determine Malaysian biotechnology industries' requirements on the generic skills, technical skills and academic skills, with the aims to identify a list of skill standards that may act as a guideline for the biotechnology educators, students, employers, and employees. This study had employed qualitative and quantitative research design with a survey instrument to collect data. Purposive sampling was conducted by which 41 out of 66 respondents had replied the 5-point Likert-scale questionnaire. Both descriptive and inferential statistics were employed in analysing the data. It was found that generic skills served as the most fundamental pre-requisite in Malaysian biotechnology industry nowadays. This was followed by technical skills and lastly, academic skills. Interestingly, it was found that there was significant difference on technical skills requirements between agriculture and healthcare biotechnology; and between industrial and healthcare biotechnology. Upon data analysis, findings from this study were successfully validated by three high profile biotechnology stakeholders with different working experiences and educational backgrounds, through semi-structured interviews. Hence, validated skill standards depicting biotechnology industrial requirements on generic skills, technical skills and academic skills were generated. The skill standards can serve as useful reference for biotechnology curriculum development, job training design, and biotechnology occupational skill standards setup.